Span Length Variance Effect on the Fatigue Life of FRP Bridge Deck - Ki-Tae Park; Young-Jun Yu; Hyunseop Shin (Advances in Materials Science and Engineering)
Fiber reinforced composite materials have the merits of light weight and durability for bridge deck and are estimated to be superior in economy to conventional deck materials considering the life-cycle cost of bridge. In this study, fatigue tests were conducted for the span lengths of 2.0 m and 2.5 m in order to investigate the change trend of fatigue characteristics of composite material deck according to the change in the span length. The result showed that the fatigue life rapidly reduces to about 25% when the span increases by 25%. However, considering that the fatigue performance safety margin was approximately 1.6 times more than the design axle load of the DB-24 design truck load in Korea, even at the span of 2.5 m, it is judged that the FRP decks being considered can be effectively used at a span length of 2.5 m.